Simulation of the Inventory Process in a Postharvest of Export Roses Under a Business Process Management Approach [Simulación del Proceso de Inventarios en Una Poscosecha de Rosas de Exportación Bajo Un Enfoque de Business Process Management] - Sepulveda-Rojas, J (Corporacion Colombiana de Investigacion Agropecuaria Corpoica, 2023)
Few companies in the Colombian floriculture sector manage their inventories, causing stock breaks, causing downtime in key post-harvest operations, causing non-compliance with sales orders and damage to the flower. For this reason, the general objective is to simulate the inventory process handled in the postharvest of rose (Rosa sp.), to find opportunities for improvement. This research work was a case study carried out in an export company of rose bouquets from Cundinamarca, the province with the largest volume of export-type flower production at the national level. The rose postharvest was selected by the indicators of low production. Because this is a descriptive and exploratory investigation, a modeling of the inventory process was carried out, with the help of the managers and an analysis of times and probability of occurrence of the tasks involved. Subsequently, the simulation was done with the inventory process cycle time in Bizagi Modeler®, making a total of 36 réplicas. This resulted in a total inventory process cycle time of 9,684 minutes for the Valentine s season, finding that 44 % of the activities can be optimized. Finally, it is concluded that, with the simulation of the inventory process, non-value- added activities can be found, serving as an input in the development of improvement strategies. © 2023 Corporacion Colombiana de Investigacion Agropecuaria Corpoica. All rights reserved.